(untitled) (Acta Scientiarum. Agronomy, 2025)
This study investigated the enhancement of fruit-related traits in dwarf tomato populations through advanced hybridisation strategies, employing UFU MC TOM1 as the donor parent. This experiment was conducted at the Federal University of Uberlândia’s experimental station over 3 production cycles from 2019 to 2021. Crossbreeding and backcrossing were performed using UFU-57 as the recurrent parent and UFU MC TOM1 as the donor parent, and dwarf plants were selected in the BC1F2 and BC2F2 generations. This research focused on improving key fruit quality attributes, including size, acidity, and phytonutrient levels, such as Î²-carotene and lycopene. Notable improvements were observed, particularly in the second backcrossing generation, which produced salad-type fruit with enhanced traits. Promising populations, including UFU Ã— DTOM 8#2-3, UFU Ã— DTOM 22#1-17, and UFU Ã— DTOM 4#4-14, demonstrated significant potential for further lineage development and hybrid breeding programs. Metabolomic analysis identified increased levels of glycine, myo-inositol, acetamide, and dodecanoic acid in the dwarf salad-type tomato line, which were likely associated with improved stress resilience, enhancing its potential for breeding robust cultivars. These results provide a crucial understanding of the genetic mechanisms underlying fruit quality improvement and stress resistance in dwarf tomato. These findings highlight the potential for developing superior cultivars that combine improved nutritional quality with enhanced resilience to biotic and abiotic stressors, thereby contributing to sustainable agricultural practices and food security.